Correlation of Creatinine Clearance Calculated by Cockcroft & Gault Equation and 24-hour Urine Collection in Gynecologic Cancer Patients - Somsook Santibenjakoon; Nakarin Sirisabya (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
Objective To study the correlation between creatinine clearances, calculated by Cockcroft & Gault equation, and 24-hour urine collection in gynecological cancer patients treated with carboplatin. Materials &Methods Thirty-eight gynecological cancer patients who were treated with carboplatin at King Chulalongkorn Memorial Hospital from March 2008 to May 2009 were recruited. Creatinine clearances calculated by Cockcroft & Gault equation and 24-hour urine collection were compared. Data regarding age, height, lean body weight, and serum creatinine were also recorded. Result The mean age of the patients was 51.1 (SD = 8.4) years. The mean serum creatinine was 0.58 (SD = 0. 12) mg/dl. The mean creatinine clearance that was calculated by Cockcroft & Gault equation was 90.2 (SD=19.0) ml/min compared to 99.5 (SD = 21.8) ml/min estimated by 24-hour urine collection. Pearson correlation coefficient (r) between creatinine clearance calculated by Cockcroft & Gault equation and 24-hour urine collection was 0.61 (p < 0.01). Conclusion Moderate correlation between creatinine clearances calculated by Cockcroft & Gault equation and 24-hour urine collection in gynecological cancer patients was demonstrated.